Apolipoprotein E genotypes modulate neuroinflammatory and vascular pathology in hyperhomocysteinemia‐induced VCID. (1st February 2022) - Seaks, Charles E; Weekman, Erica M; Sudduth, Tiffany L; Bottiglieri, Teodoro; Johnson, Lance A.; Wilcock, Donna M
Abstract: Background: Vascular contributions to cognitive impairment and dementia (VCID) are a major cause of dementia worldwide. Studies have shown Apolipoprotein E (ApoE) genotype is a risk factor for VCID in humans. Our lab has previously demonstrated recapitulation of aspects of human VCID using a hyperhomocysteinemia (HHcy)‐inducing dietary model in mice. The goal of this study was to assess the impact of ApoE genotype on the vascular pathology and neuroinflammatory changes generated by the induction of HHcy. Method: Humanized ApoE3/3 and 4/4 mice were aged to 6 months and placed onto an ad libitum diet of either HHcy inducing diet, or a nutritionally normal Control diet. The groups; E3/3 Control (n=14), E4/4 Control (n=15), E3/3 Folate (n=20), and E4/4 Folate (n=15); were balanced for sex. After 12 weeks on diet, tissue was harvested and assessed. Histological analyses for IBA‐1, GFAP, and Prussian Blue were performed. RNA was extracted from frozen hippocampal tissue. We performed the NanoString Mouse Neuroinflammatory Panel, as well as qPCR for inflammatory genes and matrix metalloproteinases. Plasma and brain tissue were analyzed for homocysteine‐relevant metabolites via LC‐MS/MS. Result: We observed significant differences in Iba1 between E3/3 HHcy and E4/4 HHcy groups, with E3/3 HHcy being more activated than the E4/4 HHcy. No differences in GFAP staining was observed between groups. Diet and ApoE genotype‐ dependent differences were also observed in a number of additional inflammatory genes, including TREM2, CD86, TNFa, and IL1b. Finally, metabolomics revealed a muted response to HHcy‐inducing diet in the E4/4 mice compared to the E3/3 mice, suggesting altered homocysteine metabolism due to ApoE genotype. Conclusion: Our results demonstrate significant differences in how ApoE3/3 and ApoE4/4 mice respond to HHcy conditions on a pathological, gene expression, and metabolic level. Our neuroinflammatory data suggest that the ApoE4 mice were less reactive to neuroinflammatory stimulus than their ApoE3/3 counterparts.